Answer with explanation:
The force of gravity between two objects is given by
![F_(g)=(-Gm_(1)m_(2))/(r^2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ax5994exblosrypvvfyplf7yk4m7ncqxn1.png)
Replacing , force by , y and product of -G the gravitational constant, masses
by t,the above equation reduces to,
![y=(t)/(x^2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/skmpsa0dylqcgvfgd7blgd3d06ve96imwu.png)
Horizontal Asymptote, is, y=0
![y= \lim_(x \to \infty) f(x)\\\\y = \lim_(x \to \infty) (1)/(x^2)\\\\y=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/7n0itveph5rkcr9pbsclr6fjvgznupxq3o.png)
And Vertical Asymptote is, x=0
![x= \lim_(y \to \infty) f(y)\\\\x = \lim_(y \to \infty) (-1)/(√(y))\\\\x=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/rkek1dq133hosw4j6kc7ojzqssj68jdox7.png)
The meaning of vertical asymptote in context of the graph of the function is ,that when Distance between two objects reduces to Zero, the force of attraction between two bodies, reduces to zero.